Survival Analysis of Time to Cardiovascular Disease Complication of Hypertensive Patients at Felege Hiwot Referal Hospital in Bahir-Dar, Ethiopia: A Retrospective Cohort Study - , Melaku Tadege Gesese (Archives of Current Research International, 2017)
Background: Cardiovascular disease complication is the current issue throughout the world. Objective of the Study: The aim of this study was to analyze the major risk factors which lead to cardiovascular disease complication in hypertensive patients. Method: A retrospective cohort study with one hundred fifty three hypertensive patients have been taken from a hospital record at the Felege Hiwot Referral Hospital, Bahir Dar, Ethiopia, during 2012 to 2016. Kaplan-Meier comparison and Cox proportional hazard model were applied. Results: From the long rank test result, Patients who had baseline cardiovascular disease significantly differ from patients who hadn’t complication for a shorter cardiovascular disease complication time. From the Cox regression result, the risk of developing cardiovascular complication rises 3.7%, when a single year increment of age (p value=0.0486). The possibility of a patient to develop cardiovascular disease who lives in rural area was 0.377 times lower than a patient who lives in urban area (P value=0.0275). The risk of developing cardiovascular complications in a short period was 8% and 6%, depending on 10 MmHg increment of systolic and diastolic blood pressure respectively. Patients who had baseline complication were found to be associated with shorter survival time within their pain, that hazard ratio was 4.684 times than that of patients who had not baseline complication (P value=0.0004). Conclusion: From the Cox proportional hazard model, there were five major factors that affect the cardiovascular disease complication time of hypertension patients. Those are: residence, baseline cardiovascular complication status, baseline diastolic blood pressure, baseline systolic blood pressure and baseline age at 5% significance level.